Pengaruh TPT, IPM Dan Pendidikan Terhadap Penduduk Miskin Di Sumatera Utara - Ajeng Windi Astuti; Era Widia Br Sinaga; Ilman Ashari; Nazwa Fazirah Nasution; Nur Aini Simbolon (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Poverty is an issue that is often discussed by society. This research aims to analyze the influence of the level of open poverty, human development index, and level of education on poverty in North Sumatra Province. Using the panel data regression method, the research results show that the human development index and education level have a significant influence on poverty, while the level of open poverty does not have a significant influence. These findings provide important insights for policy makers in designing more effective and sustainable poverty alleviation programs in North Sumatra.